FORMATION OF ACCOUNTING POLICY FOR INVENTORIES AT RESTAURANT ENTERPRISES - BULAT, GALINA; GUMENYUK, ANTONINA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
According to the results of expert analyzes, the total number of restaurant enterprises has increased by 30–40 % over the last three years. This positive trend suggests that the number of restaurants will continue to grow in various segments.Most experts researching the industry argue that most restaurants can be classified into one of two categories: full-service and specialty.Regardless of the classification group to which the restaurant belongs, its economic activity can be divided into the following operating cycles: the implementation of logistics operations for the purchase of goods (raw materials) to ensure the continuous operation of the institution; ensuring the preservation of inventories in the warehouse and the organization of warehouse accounting; transfer of products and goods to the kitchen and the process of production of finished products and dishes; transfer of own products and goods to the bar or dining room in order to sell finished products and purchased goods to consumers.Therefore, the state of inventories, the peculiarities of their formation and use is a determining factor in ensuring the competitiveness of restaurant enterprises. Because, it is inventories that make up most of the current assets of such enterprises.At the same time, the reflection of inventory transactions in accounting allows you to make inventory management more efficient. In turn, the process of analysis allows to systematize information on the movement of inventories so that it is more clear and useful to managers at different levels.Consequently, a successful combination of accounting and analysis of commodity transactions, thus the formation of effective accounting and analytical support will be the basis of correct and economically sound purchasing policy of the restaurant business.
Keywords: accounting policy; inventories; document; restaurant business; turnover; transport and procurement costs; order on accounting policy